Tribotechnical descriptions of ceramet carbon composition materials / V.A. Skachcov, O.S. Vodennikova // Problems of Tribology. – 2012. – № 1. – Р. 113-115. - Скачков, В.А.; Воденникова, О.С. (Problems of Tribology, 2014)
The coefficients of friction of multicomponent composition materials are certain an experimental method. The estimation of adequacy of rejection of experimental values of coefficients of friction is conducted from a calculation in obedience to the developed mathematical model of prognostication.